New Realism in Chinese Fine Arts of the 1970s-1980s: Concepts and Theoretical Approaches - Tokar, Maryna; Liu, Haotian (HUDPROM: The Ukrainian Art and Design Journal, 2024)
The aim of this article is to examine the concept of new realism and the theoretical approaches to its study within contemporary Chinese and Western art discourse. The research is grounded in the principles of historicism and objectivity, employing methods of comparative and figurative-stylistic analysis. The article demonstrates that new realism, as an artistic phenomenon, emerged through the interaction of two conceptual approaches. The first perspective views new realism as a counterpoint to socialist realism, the latter representing the “old” system of artistic culture and the outdated practice of ideological control over artists. The second perspective interprets realism as “new” because it reflects contemporary and relevant qualities of the realistic artistic language. Furthermore, new realism introduces innovative artistic language across various genres. In a certain sense, it continues the artistic heritage of classical art, particularly neoclassicism. The authors emphasize that both perspectives actively utilize the term new realism, albeit often in differing or partially overlapping contexts. It is also important to note that realism holds particular significance within Chinese fine art. When combined with qualities of novelty and a revival of classical aesthetics, it gives rise to new forms of artistic expression. These can be observed in the formal, compositional, and figurative-stylistic elements of modern Chinese painting. The article explores the challenges surrounding the formation and evolution of new realism as a key phenomenon in contemporary Chinese art. It identifies the conceptual and terminological features, as well as the analytical directions relevant to the study of new realism in the broader context of the development of Chinese painting from the late 20th to the early 21st century. The results of the study may be applied to further scholarly research on Chinese art from this period and to the methodological practices of Ukrainian Oriental studies.